1999
DOI: 10.1097/00005110-199909000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Performance of First-Line Management Functions on Productivity of Hospital Unit Personnel

Abstract: Eight management functions influence the productivity of unit personnel differently. Although leadership of the first-line manager is the primary driving force, time and effort expended in operations detract from this unit output. Better use of second-line managers is a choice strategy to enhance productivity. Benner's model of professional development, in combination with the creation of a first-second line shared leadership operational framework, is recommended, with follow-up evaluations on unit productivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 11 publications
2
29
0
Order By: Relevance
“…clinical directorate managers and unit nurse managers). The settings of the study were mostly trust or hospital-wide; a few articles were set in specific settings or contexts: elderly care,40 evidence-based medicine,41 staff productivity,42 clinical risk management43 and hospital-acquired infection prevention 44. Two studies involved specific interventions,45 46 and 7 studies concentrated specifically on QI rather than quality and safety oversight or routine 35…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…clinical directorate managers and unit nurse managers). The settings of the study were mostly trust or hospital-wide; a few articles were set in specific settings or contexts: elderly care,40 evidence-based medicine,41 staff productivity,42 clinical risk management43 and hospital-acquired infection prevention 44. Two studies involved specific interventions,45 46 and 7 studies concentrated specifically on QI rather than quality and safety oversight or routine 35…”
Section: Resultsmentioning
confidence: 99%
“…However, few reported financial goals as more important than quality and safety goals,32 and health system Boards only spent slightly more time on financial issues than quality 51. Frontline managers also placed less importance and time on QI,42 identified as the least discussed topic by clinical managers 52…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leadership style has a dramatic effect on staff motivation for productivity [33], stress, job satisfaction and workforce retention [34]. Leaders who inspire and empower others are more likely to model values and ethics that are congruent with their personal manner and professional practice [24,35-37] and be aligned with the organisational values and expectations they transmit [25,38,39].…”
Section: Resultsmentioning
confidence: 99%
“…Raises, bonuses, and promotions can be used to entice workers to increase their productivity, while various punishments can be used to deter employee shirking. Empirical evidence that supervisor transactional activities can increase worker productivity have also been demonstrated in factory environments (Bass 1997;Wagner 1981) and hospital settings (Fox et al 1999). The policing research has also suggested that field supervisors influence officers' behavior.…”
Section: Literature Reviewmentioning
confidence: 96%